Tricuspid valve perforation in a child with ventriculoatrial shunt - Güngör, Serdal; Arslan, Müjgan; Karakurt, Cemşit; Raif, Sabiha Güngör (Journal of Pediatric Neurology, 2014)
Ventriculoperitoneal and ventriculoatrial shunting methods are used for the surgical treatment of hydrocephalus. However, many years or months after the treatment, complications can develop. In this article, we report on a patient with perforation of the tricuspid valve and tricuspid insufficiency, which developed as a complication of the ventriculoatrial shunt. This is a previously unreported complication in pediatric patients with a ventriculoatrial shunt. Because of fairly common and life-threatening cardiac complications, ventriculoatrial shunted patients should be monitored closely by echocardiography.
Keywords: Child; perforation of tricuspid valve; ventriculoatrial shunt